The Sexual/Political Freud with Marx, Fanon, Foucault - BERNINI, Lorenzo (Research in Sexualities, 2023)
The Sexual/Political engages with contemporary political issues in sexuality through a survey of modern philosophy, psychoanalytic thought, 20th-century political theory, and more recent queer philosophies. The book investigates how the sexual has perturbed philosophical, political, and psychoanalytic thought and how this has fed into discrimination against the LGBTQI community. It analyses the social stigmas applied to public and private sexual acts and the psychopolitical processes leading to the prevalence of neo-fascist populism in Italy and the world. Tracing the history of sexuality through Freud, Marx, Fanon, and Foucault, among many others, Bernini considers why the sexual has always been an exceptionally difficult object to consider in political theory. This book will be of key interest to scholars in queer theory; antisocial theory; psychoanalysis and politics; drive theory; political philosophy; critical theory; LGBTQIA+ issues; gender and sexuality studies; and Italian studies. The Open Access version of this book, available at http://www.taylorfrancis.com, has been made available under a Creative Commons [Attribution-Non Commercial-No Derivatives (CC-BY-NC-ND)] 4.0 license.